DOI: 10.11606/d.22.2007.tde-13112007-142942
|View full text |Cite
|
Sign up to set email alerts
|

Análise da violência doméstica entre as mulheres atendidas em uma maternidade de baixo risco

Abstract: Palavras-chave: Violência doméstica. Violência contra a mulher. Violência na gestação. Saúde da mulher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
11

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 32 publications
1
5
0
11
Order By: Relevance
“…Um outro trabalho realizado no mesmo município encontrou associação entre baixo conhecimento de epidemiologia da VCM e ser enfermeiro. 17 Esse panorama de desconhecimento da epidemiologia da VCM no pré-natal fica evidente ao se analisar um estudo realizado com puérperas de uma maternidade pública de Ribeirão Preto, SP, 18 o qual encontrou índice de violência por parceiro íntimo de 19,6% durante a última gestação; essas puérperas entrevistadas frequentaram o pré-natal na rede básica de saúde de Ribeirão Preto, e muitas delas possivelmente tiveram contato com profissionais entrevistados neste estudo; no entanto, apenas 13,7% dos enfermeiros responderam corretamente à afirmativa sobre a epidemiologia da VCM durante o pré-natal, confirmando a invisibilidade da violência sofrida por essas gestantes por parte dos enfermeiros.…”
Section: Discussionunclassified
“…Um outro trabalho realizado no mesmo município encontrou associação entre baixo conhecimento de epidemiologia da VCM e ser enfermeiro. 17 Esse panorama de desconhecimento da epidemiologia da VCM no pré-natal fica evidente ao se analisar um estudo realizado com puérperas de uma maternidade pública de Ribeirão Preto, SP, 18 o qual encontrou índice de violência por parceiro íntimo de 19,6% durante a última gestação; essas puérperas entrevistadas frequentaram o pré-natal na rede básica de saúde de Ribeirão Preto, e muitas delas possivelmente tiveram contato com profissionais entrevistados neste estudo; no entanto, apenas 13,7% dos enfermeiros responderam corretamente à afirmativa sobre a epidemiologia da VCM durante o pré-natal, confirmando a invisibilidade da violência sofrida por essas gestantes por parte dos enfermeiros.…”
Section: Discussionunclassified
“…Other studies in various regions of Brazil and in other cities of the state of São Paulo showed similar results. (9,10,16,(20)(21)(22)(23) Among the women of this study that were exposed to intimate partner violence, almost half of them reported psychological violence, which is almost the triple of physical violence (18.4%) and ten times higher than sexual violence (4.8%). This higher percentage of psychological violence in detriment of the other types was similar to other studies and indicates that reports of violence have been obtained thanks to the access to information, human rights, establishment of institutions to protect women and awareness of the female population.…”
Section: Discussionmentioning
confidence: 74%
“…This higher percentage of psychological violence in detriment of the other types was similar to other studies and indicates that reports of violence have been obtained thanks to the access to information, human rights, establishment of institutions to protect women and awareness of the female population. (16,20,21,24) Both Brazilian and international studies show high rates of intimate partner violence. (6,7,21,23,25) The episodes of violence can be severe, recurrent, and overlapping.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations